Središča moči japonske družbe - Ferfila, Bogomil (Teorija in praksa, 2000)
Characteristics of three major Japanese power centres - business, parliament and state bureaucracy - are mutual dependence and connection. In comparison with the structure of power centres in European and Australasian states, Japan lacks one specific block - labour or its trade union representatives. All the employed in Japanese corporations must be unconditionally subordinated to the needs of the company, no matter whether they are members of managing board, managers or the employees. "Corporative soldiers" must in almost military way subordinate their interests to the interests of corporation. In exchange, every summer and winter the corporation "as superior being" pays out bonus, depending on efficiency of business and sometimes reaching the amount of few-month (even six-month) salary. It is well-know that the governmental bureaucracy played an important role in Japanese economic miracle- it was a sort of generator of economic reforms. For this purpose, talented graduates from Japanese universities were recruited as career governmental employees. The key factor were their managerial abilities and the government have stimulated them by giving them high official positions, power and reputation. The many years' strategy of the conservative LDS government was to encourage industrial and technological development to detriment of social security programmes. From the perspective of national economy this strategy seems to be useful since it has encouraged households to maximal economising to ensure the money for retirement, and also more expensive housing and education.
Keywords: Japonska; korporacije; podjetja; podjetništvo; economy; gospodarstvo; sindikati